Eosinófilos como células apresentadoras de antígeno durante a infecção experimental por toxocara canis - Rodolpho, Joice Margareth de Almeida (Universidade Federal de São Carlos, 2017)
Eosinophils are multifunctional cells that have pro-inflammatory cytotoxic activities and stimulate CD4 + T cells in experimental models of allergy and parasitic infections. Eosinophils, when exposed to antigens are activated and express CD38 / CD69 molecules and exhibit increased expression of the Major Histocompatibility Complex (MHC-II), CD80 and CD86, suggesting their role as atypical cells in the Presentation of Antigens. In the present study, we evaluated the hypothesis that, in addition to professional APCs (monocyte, dendritic and B cell), eosinophils are activated by Toxocara canis antigens and express a range of cell surface markers characteristic of antigen presenting cells. Thus, contributing to the immune responses induced in the experimental model by Visceral Migrans Larva syndrome associated with T. canis infection (VLMS). By means of flow cytometric assays the cell profiles of antigen-presenting cells were evaluated during T. canis experimental infection. Data analysis demonstrated that, during murine T. canis infection, peripheral blood, spleen and bone marrow eosinophils showed regulated expression of CD69 / MHC-II / CD80 / CD86, assuming a role as APC in comparison with the antigen presenting cells. Unlike eosinophils of the spleen and bone marrow, circulating eosinophils showed increased expression of activation markers along with APC-related molecules after T. canis infection. The same activation was not observed for professional APCs in the same compartments. Improved connectivity between eosinophils and T cells in T. canis infected mice in all three compartments (peripheral blood, spleen and bone marrow) also supports the hypothesis that eosinophils may play a role as PCA during T. canis infection. In addition, in vitro stimulation of T. canis antigen resulted in activation and elevation of regulation of APC-related molecules by eosinophils derived from bone marrow. These findings strongly suggest that T. canis infection reshapes eosinophils to act as APCs in this infection and not only as an effector cell in the control of parasitic infection.
Eosinophils as antigen presenting cells during toxocara canis experimental infection
Keywords: Eosinófilos; Células apresentadoras de antígeno (APC); Toxocara canis; SLMV; Moléculas co-estimulatórias; Eosinophil; Antigen-presenting cell (APC); Toxocara canis; SLMV; Costimulatory molecules; CIENCIAS DA SAUDE